Comparative study of lameness in crossbred cows on sand and pucca floor - SINGH, SUSHIL KUMAR; LATHWAL, S S; KASWAN, SANDEEP; DEVI, INDU (The Indian Journal of Animal Sciences, 2017)
A total of 40 (20 normal and 20 lame) lactating crossbred Karan Fries cows were randomly divided, considering their age, stage of lactation and parity, into four equal groups so as to rear on sand and pucca floor. Therefore, each group of sand and pucca floor included 10 normal and 10 lame cows for comparative study. All the lactating cows were recorded for milk fat %, rumen pH and lying time at fortnightly interval to find out existence of any kind of association with lameness. Parameters were recorded from each animal at fortnightly interval for duration of four months. Locomotion score of all the animals was recorded by visual examination of posture and gait of cows. Rumen pH was significantly (P